EVALUATION OF WHITE-LIPPED PECCARYS [Taiassu pecari (Link., 1795)] PROGESTERON AND STRADIOL CERUM LEVELS AND FEMALE GENITAL TRACT STRUCTURE - MANGINI, Paulo Rogério (Scientia Agraria, 2000)
Biological diversity and the preservation of native animal species has become a matter of increasing concern. This leads to an increase in research aiming at solving problems due to the growth of human population. This study evaluates morphologic and histological characteristics of ovaries, uterine tubes, uterus, cervix and vagina, as well as serum progesterone and estradiol levels in 15 female white-lipped peccaries (Tayassu pecari). All animals were born in a commercial farm in Quedas do Iguaçu - PR, BRAZIL (52º 54 W; 25º 26 S). The area is characterized by the transition from an Ombrofila Mixed Forest to a Semidecidual Stational Forest. All individuals were killed and corporal mass, reproductive tract mass, ovarian, uterine, cervical and vaginal length and diameter and uterine tube diameter were measured. Blood samples were collected immediately before killing and progesterone and estradiol levels were measured by solid phase radioimmunoassay (RIA). Reproductive tracts were sampled and histological structures were evaluated. Samples were classified, according to histological characteristics, in pregnant (n=1), follicular (n=1), early luteal (n=2) and mid-luteal (n=11) phases. The average corporal mass was 26.23 ± 3.62 kg. Average reproductive tract mass was 77.65 ± 23.47 kg. Right ovaries measures were as follows: craniocaudal length 14.32 ± 2.15 mm; dorsoventral length 13.68 ± 2.18 mm and laterolateral length 9.68 ± 1.60 mm, while left ovaries measures were: craniocaudal length 12.81 ± 1.45 mm; dorsoventral length 11.58 ± 1.88 mm and laterolateral length 8.58 ± 1.16 mm. The cervical length was 30.89 ± 12.34 mm and the external diameter was 18.62 ± 4.16 mm. Vaginal length was 144.00 ± 26.67 mm and the external diameter was 26.23 ± 4.30 mm. Uterine length and diameter varied significantly, according to the categories diameter in the median portion of uterine horn ranged from 5.4 to 35 cm and the length from 10.0 to 34.0 cm. Hormonal levels were significantly different among the categories: estradiol levels ranged from 131.26 to 31.06 pg/ml and progesterone from 1.00 to 17.21 ng/ml. Follicular and luteal bodies diameters, as seen on ovarian surface, did not prove to be efficient evaluation parameters in determining estral cycle phase. Hormonal concentrations were compatible with histolagical structures, which confirms the efficiency of both the RIA hormonal analysis method and also histological evaluation in determining Tayassu pecaris reproductive capacity and estral cycle phase. The species precocity while in captivity was also proven with reproductive capability starting at eight months of age.